Evaluation of aPTT and PT Results: A Comparison Between Point-of-Care Testing and Optical Fully Automatic Methods - Herna Wahyuni; Dewi Indah Sari Siregar; Ranti Permatasari; Nindia Sugih Arto; Malayana Rahmita Nasution; Jelita Siregar (Indonesian Journal of Global Health Research, 2026)
A coagulometer is a tool used to check coagulation parameters, such as prothrombin time (PT) and activated partial thromboplastin time (aPTT), for which there are currently various detection methods. Examining PT and aPTT coagulation function requires a fast turnaround time and immediate results because the stability of coagulation factors is less than four hours, so a fast and precise examination is needed. Point-of-care testing (POCT) is a good alternative. This study aimed to determine the difference in aPTT and PT values between POCT and optical fully automatic. This comparison will be useful when selecting coagulometer devices. Methods: This study used a cross-sectional study with a non-probabilistic sample of 100 citrate samples. Each sample was tested for aPTT and PT using POCT and optical fully automatic testing. The results of each examination were analyzed using the Mann–Whitney, Bland-Altman Plot, and correlation statistical tests. In this study, precision tests were also carried out on both methods. methods. There was a significant difference (p < 0.001) in the comparative test results for the aPTT and PT values obtained using the POCT method compared to the optical fully automatic method. The average difference between the two methods was 6.6 seconds for the aPTT parameter and 4.98 for the PT parameter. Fourteen samples were found to have different interpretation values for the aPTT parameter, and 28 samples for the PT parameter. There is a significant difference between the POCT method and the optical fully automatic method. The precision test on the POCT method produced good results.